The im portance of blood proteins and glutaraldehyde coagulation test in the diagnosis of calves suffered from pneumo-enteritis - Veysi Aslan; Mahmut Ok; Mehmet Maden; Mutlu Sevinç; Firuze Kurtoğlu (Eurasian Journal of Veterinary Sciences)
Fifteen healthy calves, sixteen calves with enterilis infections and seventeen calves, with pneumonia infections were usedin thes study. Clinical and laboratory examinations (Serum total protein, albumin, globulin and plasma fibrinogen levels, leucocyte counts and PCV), microorganism identification and antibiolis sensitivity and Glutaraldehyde test were performed. The differencies between albumin and fibrinogen rate of healthy calves and calves with enteric infections were found mo re significantly (p<0.01 ). The differents between albumin, leucocyt counts and fibrinogen rat e of healthy and calves with pneumonia infections were found more significantly (p<0.01 ). Results of study showed that elinical findings, microorganism isoiate and GA test, albumin, fibrinogen and leucocyt counts could be mo re significant (p<0.05) in the diagnosis of enteric and pneumonia infections.